Encyclopedia of life : explore the breadth of life on Earth - Kelly, Miles (Essex : Miles Kelly Publishing Ltd., 2014)
Encyclopedia of Life is a fantastic resource for children aged 8+, covering the breadth of life on our planet. Split into eight sections, it provides a detailed guide to the following topics: Prehistoric Life, Plants, Water Life, Insects, Reptiles and Amphibians, Birds, Mammals and the Human Body. Top features include visual fact files, bulleted facts, charts, world records, bizarre facts and top tens. The book is fully cross-referenced throughout and is packed with diagrams, illustrations and photos.
Includes index
Keywords: Reference; Life; Encyclopedia